ANALISIS KESALAHAN BERBAHASA INDONESIA PADA ARTIKEL BLOG KOMPASIANA "KEKERASAN SEKSUAL DAN RUNTUHNYA MURUAH PESANTREN? - Kartini Pangaribuan, Widya; Novianti Sinurat, Lestari; Mutianda, Livia; Sevtia Br Karo-Karo, Dear; Tamara, Riby; Erawati, Yolani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze Indonesian language errors in a Kompasiana blog article entitled "Kekerasan Seksual dan Runtuhnya Muruah Pesantren?" by Idris Apandi. The research employs a descriptive qualitative approach with listening and note-taking methods. Data were analyzed based on The Enhanced Spelling of the Indonesian Language (EYD) and the Great Dictionary of the Indonesian Language (KBBI). The findings revealed 12 errors classified into four categories: non-standard word usage (4 findings), ineffective sentence construction (4 findings), capitalization errors (2 findings), and punctuation errors (2 findings). Non-standard word errors include the use of "muruah" (should be martabat), "trainer" (should be pelatih), "platform" (should be sarana), and inconsistent writing of "kyai/kiai". Ineffective sentence errors include the use of "digeneralisasi", the phrase "ikut dicap buruk", as well as typos and wordiness. These findings indicate that blog platform writings tend to have higher error rates due to the absence of a rigorous editing process.